2014
DOI: 10.1159/000368405
|View full text |Cite
|
Sign up to set email alerts
|

Asthma: The Role of Low High-Density-Lipoprotein Cholesterol in Childhood and Adolescence

Abstract: Background: Several studies have examined the relationship of asthma with serum dyslipidemia and reported positive, negative or no association. Most studies were limited by their cross-sectional design and the wide age range of the participants. In a cohort of children in Cyprus, we explored the association of asthma with serum high-density-lipoprotein cholesterol (HDL-C) at age 16-18 years (follow-up) independently of and in relation to HDL-C at age 11-12 years (baseline). Methods: In a case-control design, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…9 In contrast, a study in adults found that asthmatic patients had lower levels of both total cholesterol and triglycerides, 10 and a recent study found that adolescents with asthma and recurrent wheeze had lower HDL-C levels. 29 However, the asthma diagnosis in all of these previous studies is based on unspecific questionnaires filled out by the patient or the patient's parents, and none of them include lung function data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In contrast, a study in adults found that asthmatic patients had lower levels of both total cholesterol and triglycerides, 10 and a recent study found that adolescents with asthma and recurrent wheeze had lower HDL-C levels. 29 However, the asthma diagnosis in all of these previous studies is based on unspecific questionnaires filled out by the patient or the patient's parents, and none of them include lung function data.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that asthmatic patients have a decrease in HDL-C levels from childhood to adolescence, 29 which could indicate that the distinct lipid profile acts as a biomarker for the degree of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in a case-control design, Yiallouros et al [41], using a logistic regression model, evaluated a possible link between serum HDL levels and asthma in active asthmatic ( n = 68) and current wheezer ( n = 123) populations. A significant trend of decreased serum HDL levels was detected in the asthmatic group compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, development of ALI alone did not affect these plasma lipoproteins (Table 2, left), although patients with asthma often have higher plasma LDL and lower plasma HDL than those from control patients. 38,39 Interestingly, data revealed that ALI significantly increased plasma LDL and decreased plasma HDL without affecting plasma total cholesterol levels in mice that developed concurrently atherosclerosis (Table 1, left). These observations remain consistent to what was reported in humans.…”
Section: Discussionmentioning
confidence: 99%